Performance Optimization through Motivation Analysis in MFIs: A Journey through Arusha, Tanzania - Stephen Jeuma Bakari (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
The study aimed to investigate the influence of extraneous motivators on the performance of staff in Tanzanian microfinance institutions. Data from 98 non-deposit-taking microfinance institutions in Arusha was analyzed using descriptive statistics and Pearson Coefficient Correlation to assess the impact of incentives, rewards, and salary packages on employee performance. The findings indicated that employee incentives, prizes, and salary packages significantly influenced staff performance, emphasizing the importance of extrinsic motivators in encouraging workers to perform effectively. The study’s implications for practitioners and policymakers in the microfinance industry were highlighted, emphasizing the need to enhance extrinsic incentives to motivate employees. The study also recommended further research to explore a comprehensive list of factors influencing employee performance and broaden the geographic scope beyond the Arusha region.